Development Strategies For Halal Tourism In Indonesia Through The Smart Tourism Approach - Hidayat Hidayat (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Halal tourism in Indonesia has experienced rapid growth and has become a strategic sector in the economic and cultural landscape. In an effort to maximize this potential, the smart tourism approach has become the foundation for a holistic development strategy. The aim of this writing is to provide a comprehensive overview of the development strategy for halal tourism in Indonesia through the smart tourism approach. By analyzing its progress, identifying challenges, and formulating solutions, this writing aims to offer a profound and solution-oriented perspective. This article is a literature review utilizing qualitative methods. Document data is collected from relevant journals and books and analyzed using content analysis methods. The research findings indicate that the smart tourism approach, through the utilization of digital technology, engagement with local communities, and strengthening infrastructure, is key to the success of halal tourism development. This integrated solution not only creates significant economic opportunities but also supports cultural preservation, positioning halal tourism as an inclusive and competitive sector on a global scale.